Family-centered early intervention: A concept analysis to guide pediatric and community nursing practice - Mardiyanti Mardiyanti; Yeni Rustina; Nani Nurhaeni; Nur Agustini (Belitung Nursing Journal, 2026)
Background: Family-Centered Early Intervention (FCEI) is increasingly recognized as a framework for promoting child development and family empowerment. However, its application in nursing practice may be limited by the lack of a clear distinction between FCEI, Family-Centered Care (FCC), and Patient- and Family-Centered Care (PFCC). Objective: To clarify the concept of FCEI and distinguish it from FCC and PFCC by identifying its defining attributes, antecedents, consequences, and empirical referents. Methods: Walker and Avant’s eight-step concept analysis method was applied. A comprehensive search was conducted across five databases (PubMed, CINAHL, Scopus, ERIC, and Taylor & Francis) for studies published between January 2010 and September 2025. After screening, 49 of 1,958 identified records were included. Results: Seven defining attributes distinguished FCEI from FCC and PFCC: family capacity building, caregiver-mediated intervention (coaching), natural environment-based delivery, routines-based intervention, timeliness and early action, orientation toward developmental and functional outcomes, and an enabling system. These attributes position families as the primary agents of developmental change and situate intervention within everyday routines and natural environments. Antecedents included developmental screening, coordinated service systems, and provider coaching competencies, while consequences encompassed improved child developmental outcomes, greater parental self-efficacy, enhanced family quality of life, and stronger service coordination. Conclusion: FCEI is a distinct developmental intervention framework that extends family-centered principles beyond clinical care toward caregiver coaching, family capacity building, and developmental support in everyday contexts. Integrating FCEI into pediatric and community nursing may strengthen early identification, family empowerment, and coordinated developmental care, particularly in low- and middle-income countries.